Use of hormones and nutritional supplements among gyms' attendees in Riyadh - Sulaiman A Alshammari; Mishal A AlShowair; Abdulmalik AlRuhaim (Wolters Kluwer Medknow Publications, 2017)
Background: Worldwide, studies have shown a high prevalence of hormones and nutritional supplement use by athletes and gym members. Many athletes consume unproven, potentially harmful or even banned supplements. Objectives: To assess the prevalence of the use of hormones and nutritional supplements by people who exercise in gyms in Riyadh, Saudi Arabia, and the types of supplements they most commonly use and to obtain a general view of the main reasons for using these enhancements. Materials And Methods: A cross-sectional study using a self-administered questionnaire was conducted at gyms in Riyadh that were selected randomly from different sectors of the city. The sample size was estimated at 289, but the actual number of randomly selected participants in the study was 457. Results: The number of gym members who participated in this study was 457. Approximately 47.9% of the sample reported an intake of nutritional supplements and 7.9% reported that they took hormones. Protein powder was consumed by 83.1% of the participants. Approximately 16.8% of supplement users had noticed some side effects, and 25.7% of those who took hormones had stopped taking them because of adverse effects. Only half of the hormone users (54.2%) reported that they had had medical checkups. The major source of information on supplement and hormone use was non-health professionals; friends being major source (40%) of information on the use of hormones. The use of nutritional supplements was significantly associated with BMI (OR = 1.89, CI = 1.06-3.39), duration of daily exercise (OR = 4.23, CI = 2.06-8.68), and following a special diet (OR = 8.42, CI = 5.37-13.2). There was a very strong association between nutritional supplement consumption and hormone use (P < 0.001). Conclusion: Approximately half of the participants who regularly exercised in gyms took nutritional supplements, and most had received their information from nonhealth professionals. There was an association between the duration of exercise and the use of hormones and supplements. Fewer than half of hormone users had obtained a health-care provider's advice before taking it. The atmosphere in the gym can play an important role in members' decisions. Educating gym employees and members may have a positive influence on the use of supplements and hormones.